Fetal therapy in the Dominican Republic: perinatal view - Diaz-Primera, Ramiro Jesús (2024)
Some 10% of pregnancies will qualify as high obstetric risk and will present somematernal or fetal complication. In the Dominican Republic, with a birth rate of 166,938in the year 2022, many of these births merit the participation of a maternal-fetalmedicine team. The need to form a physical and human fetal therapy unit is becomingmore visible every day in all countries in the world. The Dominican Republic has notbeen the exception, having managed to form the Dominican fetal medicine team,with a multidisciplinary perinatal vision of integration of maternal fetal medicineand pediatric subspecialties in a single team. Considering the economic rates of ourLatin American countries, excluding a country from this service forces the patientto search international treatment, representing a limitation for a very vulnerablepopulation. Thanks to the Dominican medical commitment and its public and privateauthorities, today Dominican fetal surgery is advancing under the banner ‘Health forour people, from our people’.